PENGARUH PENATAAN ULANG DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI PASAR BUNGA KALISARI SEMARANG - Kristiga Wituhu; Apriatni Endang Prihatini (Universitas Diponegoro, 2018)
Every business requires any organization influential marketing strategy essential to achieve success. Marketing strategies have a role in improving purchasing decisions through the variables that affect itself, including the rearrangement and also the price. Based on the problems in this research, that is the decrease in purchase decisions at the flower market kalisari Semarang caused by consumer inconvenience when shopping at the flower market the kalisari slums and untidy. The purpose of this study is to determine the influence of re-arrangement and the price . The type of this research is explanatory research, with 100 respondents in a kalisari flower market as the population. The technique of sampling using a purposive sampling. Using questionnaires as data collecting technique. The data analysis conducted quantitatively with SPSS. This research concluded that the rearrangement and price have positive effect on purchasing decisions. Rearrangement of variables has bigger effect that price variable. Based on the research result, the researchers suggested to traders to be able to think creatively to solve problems occurred with new kiosk-shaped shelter with adding a canopy to keep the flower fresh, and the seller are are also advised to a ornamental flower seller in flower market Kalisari Semarang to always talk the truth every time the ornamental flower price increase, so there is no misperception.